THE SOCIALIZATION OF THE YOUNGER GENERATION AND ITS PLACE IN SOCIETY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Socialization is an interactive communication process that involves both individual development and personal influences, namely the personal reception and interpretation of all social messages, but also the dynamics and content of social influences. Thus, socialization is a complex process that is based on the theory of social learning, learning which is a fundamental mechanism ofassimilation of social experience. Although retaining a certain autonomy, man and society form an indissoluble unity, and society is generated by the relationship between its members. The socialization term is expressed in the literature by social learning, culture, etc.